Migrações no Nordeste metropolitano nas décadas de 1990 e 2000 - Marcelo de Sousa Dantas (2017)
The thesis analyzes migration to and within the Metropolitan Regions of Fortaleza, Recife and Salvador in the 1990s and 2000s. A metropolitan spatial cut highlights areas where a considerable part of the regional absorption of migrants is concentrated. These areas are the ones that present strong industrial and urban dynamics and continue to receive most of the investments in the region. The literature indicates that the household family is conditioned by physical proximity and kinship, and these elements can shape individual and group behavior, including the development of strategies that reflect the way in which families adapt to forces beyond the limits of the household. The analysis uses the household family concept and considers the relationship between different migrant household arrangements and internal migration. The use of household arrangements represents a new look at migratory studies about the Northeast, which usually focuses on the analysis of migratory flows or the individual attributes of migrants. The Demographic Census data from 2000 and 2010 were used to measure migratory flows, to delineate the profiles of migrants and to establish associations between household arrangements and types of migration. In the latter case, the Grade of Membership multivariate method was used. When the individual characteristics are the only ones used in the GoM model, a clear pattern of migration from the poles to the peripheries is observed and also that the intra-state or intra-regional displacements are predominantly composed of migrants from poorer municipalities, unlike inter-regional flows. When the variables that define the household arrangements are included, the data show that migrants in single-parent households are more likely to undertake short-distance (intra-metropolitan and intra-state) movements and to have lower per capita household income. Migrants living in households with biparental couple-child arrangements are more likely to move further away and to exhibit higher per capita household income. Finally, migrant profiles indicate a higher prevalence of displacement in the early stages of the family life cycle and suggest that women act more as tied movers or as the second migrant in the search for work. In general, a profile of greater socioeconomic fragility has been observed in the household arrangements of migrants who undertake shorter displacements when compared with those who travel greater distances, which represents progress in the understanding of the migratory patterns in the Northeast.